2013
DOI: 10.4236/me.2013.410069
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Capital in Industrial Development: The Nigerian Case (1980-2010)

Abstract: Human capital development is seen as a focal point for pivoting industrial development, for reducing the level of unemployment and increasing the supply of entrepreneurs in any economy. However, the effect of human capital on sustainable industrial development in Nigeria has not been adequately explored. In view of various policies adopted by successive governments to advance industrialization in Nigeria, the study examined the effect human capital development has had on industrial growth in the light of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
(8 reference statements)
2
4
0
1
Order By: Relevance
“…From Table 4, nothwithstanding the statistical significance at the 1% and 5% levels, respectively, the indicators of human capital -high-school education, formal training and R&Dshow that, in terms of magnitude, they have a rather low positive impact on the output of manufacturing firms. This supports Adejumo, Olomola and Adejumo (2013) and Kurre and Eiben (2013) with several implications. The first response might be to dispute the fact that education as a component of human capital is irrelevant for manufacturing enterprises since it seems to be adversely affecting the sector.…”
Section: Discussionsupporting
confidence: 85%
“…From Table 4, nothwithstanding the statistical significance at the 1% and 5% levels, respectively, the indicators of human capital -high-school education, formal training and R&Dshow that, in terms of magnitude, they have a rather low positive impact on the output of manufacturing firms. This supports Adejumo, Olomola and Adejumo (2013) and Kurre and Eiben (2013) with several implications. The first response might be to dispute the fact that education as a component of human capital is irrelevant for manufacturing enterprises since it seems to be adversely affecting the sector.…”
Section: Discussionsupporting
confidence: 85%
“…His findings revealed that recurrent expenditure on education as well as capacity building impacted significantly on economic growth, while capital expenditure on education was insignificant to the growth process. Adejumo, Olomola, and Adejumo (2013) carried out a study on the impact of human capital on industrial development in Nigeria. The study made use of the different educational enrollment rates (primary, secondary and tertiary) in order to find out if any significant positive impact using these variables are felt in the industrial sector.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Based on the error correction tool from 1978 to 2008, Olayemi (2012) claimed that government disbursement on learning has a favourable tie with the index of industrial production, while a negative association is proven with that of healthiness factor, an indicator of human wealth and capital creation in gross levels. Relying on time series data from 1980-2010, Adejumo et al (2013) dissected the context of the Nigerian economy and stated that human capital has a large impact on industry value-added.…”
Section: Human Capital and Manufacturing Outputmentioning
confidence: 99%